Можно ли Печорина заместить Гяуром в русско-польском переводе - Jóźwiak, Jolanta (Studia Rossica Posnaniensia, 2015)
This paper is devoted to the problem of replacing one Russian cultural background anthroponym that is used in Polish translations with a cultural-background element that is associated with a cultural circle other than the source and target cultures. A cognitive approach to the analyzed example allows one to understand the possibility of cultural-background’s conversion and explain translators’ individual choices.